Tourist Tourist Village Development Recycling In Perspective Theory Strukturasi ( A Study Of Tukak Villagers , Subdistrict Tukak Sadai , Bangka Southern District ) - Mely Handiati Utama; Bustami Rahman; Panggio Restu Wilujeng (Profesional Muda Cendekia Publishing, 2022)
The waste problem in Tukak Village is the background for the start of recycling activities by the village community. Furthermore, the activity was developed into a tourist attraction involving stakeholders and community participation. The purpose of this study is to analyze how the development of a recycling tourism village is and what are the inhibiting factors found in it. The theory used in this research is structuration theory. This theory explains how the involvement between agents and structures in the development of recycling tourism villages. This research was designed with a descriptive qualitative research type. The data sources used are primary data sources and secondary data sources. Data collection techniques used observation, interviews and documentation. The number of informants in this study was 11 people who were determined by purposive sampling and snowball sampling techniques. The results of this study indicate that there is a relationship between agents and structures in shaping the development of this recycling tourism village. The structures seen are the structures of significance, domination, and legitimacy. Furthermore, to explain the inhibiting factors that occur in the development of this recycling tourism village, the researcher uses Giddens reflection in explaining deroutinization. Derutinization in the development of tourist villages is analyzed using the concept of Anthony Giddens' structuration theory which distinguishes the internal dimensions of the actors, namely unconscious motives, discursive consciousness and practical consciousness.